Desarrollo de un portal web que permita mejorar la gestión y el acceso a la información para la Escuela de Informática de la Universidad Nacional de Trujillo - Alvarez Díaz, Jhon Manuel (2014)
Due to the deficit with which account the current website of Computing National University of Trujillo, in a matter of informing and providing academic students of Computer Science, National University of Trujillo services; and building on existing information technologies, the web portal for the School of Computing, National University of Trujillo was developed., which improved the management and access to information._x000D_ Throughout the development of this thesis, we have applied the RUP; and all artifacts, UML diagrams and modelamientos necessary for the further development of the Web Portal, was developed the website using the Joomla CMS._x000D_ Furthermore, the design of tests were conducted to verify the functionality of the web portal, which were satisfactory._x000D_ For the proof of the thesis, two surveys were applied to the end users of the web portal, the first survey was conducted before the implementation of the proposed web portal, where users had the old website; The second survey was conducted after completion of the proposed web portal; all this in order to demonstrate the improved management and access to information web portal. The obtained and subsequently discussed final results, they conclude that the web portal developed able to improve the management and access to information for School of Computing National University of Trujillo